1996
DOI: 10.1063/1.116480
|View full text |Cite
|
Sign up to set email alerts
|

First order gain and index coupled distributed feedback lasers in ZnSe-based structures with finely tunable emission wavelengths

Abstract: First order gain and index coupled distributed feedback (DFB) gratings were realized in ZnSe-based laser structures using direct implantation with a focused ion beam for gain-modulated structures and conventional electron beam lithography for index modulation. With both technologies, gratings with periods below 90 nm could be achieved, permitting DFB emission in the blue spectral range. Fine tuning of the emission wavelength in steps of 0.14 nm is demonstrated by sampled DFB gratings based on a periodic modula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…By increasing the pump power, a sharp lasing signal appears at 731 nm with a full width half-maximum (fwhm) of 2.1 nm (Figure a), accompanied by a clear lasing onset at 19.5 μJ/cm 2 (Figure b). As the etched film is thinner (350 nm) than the solvent assisted imprinted second-order counterpart (>600 nm), and the sample passivation time is shortened to 170 h, the obtained threshold is slightly higher due to reduced optical confinement and optical gain. , Regarding the widely accepted criterion that the lasing signal should be narrower than 1 nm, the relatively large fwhm arises rationally from the overlap of two characteristic band-tail modes with equal intensity since no phase shift is introduced in the first-order DFB cavity. In addition, the resolution of the spectrometer also limits the detected line width, as seen from the broad 800 nm scattered femtosecond laser signal. Thus, the spectrum has been additionally recorded using a spectrometer with higher resolution, yielding an fwhm of 1.8 nm that is shown in Figure S1a.…”
Section: Resultsmentioning
confidence: 99%
“…By increasing the pump power, a sharp lasing signal appears at 731 nm with a full width half-maximum (fwhm) of 2.1 nm (Figure a), accompanied by a clear lasing onset at 19.5 μJ/cm 2 (Figure b). As the etched film is thinner (350 nm) than the solvent assisted imprinted second-order counterpart (>600 nm), and the sample passivation time is shortened to 170 h, the obtained threshold is slightly higher due to reduced optical confinement and optical gain. , Regarding the widely accepted criterion that the lasing signal should be narrower than 1 nm, the relatively large fwhm arises rationally from the overlap of two characteristic band-tail modes with equal intensity since no phase shift is introduced in the first-order DFB cavity. In addition, the resolution of the spectrometer also limits the detected line width, as seen from the broad 800 nm scattered femtosecond laser signal. Thus, the spectrum has been additionally recorded using a spectrometer with higher resolution, yielding an fwhm of 1.8 nm that is shown in Figure S1a.…”
Section: Resultsmentioning
confidence: 99%
“…Due to this high spatial resolution the definition of band gap modulated gratings with periods below 100 nm are possible and were already demonstrated in blue emitting devices. 16 …”
Section: Highly Spatially Resolved Lateral Band Gap Engineeringmentioning
confidence: 97%
“…They also include mirror losses that depend on cavity optical conditions and facet coatings. 5 Because of such limitations, although the negative net gain regime and immunity against SHB had been discussed numerically; to our knowledge, no practical design containing realistic material and structural parameters for such lasers has been reported. 1 These studies have shown that under particular conditions lasing could happen even when the internal losses are more than the gain, relinquishing the second condition.…”
Section: Inversionless Distributed Feedback Semiconductor Lasers: Ultmentioning
confidence: 99%